System detecting network anomaly with visualization techniques - Haocheng ZHANG; Xiaojie WU; Xiang TANG; Runxuan SHU; Tianchen DING; Xiaoju DONG (网络与信息安全学报)
With the fast development of information technology and computer network,the scale and complexity of network security data grows rapidly.Traditional visualization techniques are no longer suitable.In addition,it designs interactive functions based on the feature of network security analysis,in order to assist the network security analyst.The existing approaches for network security visualization have some defects,which fail to provide a good indication of network security data in terms of timing and also fail to display information completely and realize user-friendly interaction.A multi-view network security visualization system was proposed,which provided the analysts of both the static status and dynamic changes of the network by combining the force-oriented model and the staged animation.It provides comprehensive information with display and filter of protocols,IP segment and port.The system on Shanghai Network database were evaluated.